2015
DOI: 10.1016/j.jjcc.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Results of catheter ablation of atrial fibrillation in hypertrophied hearts – Comparison between primary and secondary hypertrophy

Abstract: Radiofrequency catheter ablation (RFCA) was successful in restoring long-term sinus rhythm in patients with LVH due to HCM and due to secondary etiology. However, patients with HCM needed more RFCA procedures and frequently additional antiarrhythmic drug therapy in order to maintain sinus rhythm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
(35 reference statements)
1
13
0
Order By: Relevance
“…Of these, 177 were excluded as they were either duplicates or deemed unsuitable for the purpose of the meta-analysis (editorials, letters, reviews or case reports). The remaining 32 studies were carefully screened and after analysis of their abstracts and/or full-text only [14][15][16][17][18][19][20][21][22][23][24][25][26][27] (one was a conference abstract 22 ) were considered adequate for inclusion in the systematic review (figure 1). Of these, only six studies, 16 19 22-25 provided enough details to be included in the meta-analysis.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 177 were excluded as they were either duplicates or deemed unsuitable for the purpose of the meta-analysis (editorials, letters, reviews or case reports). The remaining 32 studies were carefully screened and after analysis of their abstracts and/or full-text only [14][15][16][17][18][19][20][21][22][23][24][25][26][27] (one was a conference abstract 22 ) were considered adequate for inclusion in the systematic review (figure 1). Of these, only six studies, 16 19 22-25 provided enough details to be included in the meta-analysis.…”
Section: Search Resultsmentioning
confidence: 99%
“…Figure 2 illustrates freedom from arrhythmia in patients with HCM and controls. Control patients had no structural heart disease, except for left ventricular hypertrophy secondary to systemic hypertension in Müssigbrodt et al, 25 21 or these were used in only a minority of patients. 22 However, in the remaining studies, antiarrhythmic agents were needed for optimisation of the rhythm control strategy in >25%-50% of patients with HCM.…”
Section: Procedural Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen studies were finally selected, with one study in particular including patients with tachycardiomyopathy (TCM), eight studies including patients with hypertrophic cardiomyopathy (HCM), and five studies including patients with valvular cardiomyopathy. [43][44][45][46][47][48][49][50][51][52][53][54][55][56] Observational studies. As detailed in Table 1, observational studies included 1,504 patients.…”
Section: Search Resultsmentioning
confidence: 99%
“…Concerning AF ablation outcome, eight observational studies have been conducted among HCM patients. [44][45][46][47][48][49][50][51] Consistently, all studies reported a very limited efficacy after a single ablation procedure. However, about half of the patients underwent repeated procedures, raising the efficacy up to 70% to 80%; in this respect, the prevalence of extensive LA or biatrial ablation, including linear lesions and CFAEs, was significantly higher as compared with more ''classical'' CHF patients ( Figure 1).…”
Section: -59mentioning
confidence: 90%